(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This critical study explores the postcolonial voice in Indian English poetry, examining how poets articulate their identities and cultural experiences in the wake of colonialism and globalization. The evolution of Indian English poetry from the late 19th century to the present reflects a dynamic interplay between historical context, linguistic hybridity, and thematic diversity. Early poets such as Henry Derozio and Sarojini Naidu set the stage for a burgeoning literary tradition, articulating a sense of national pride and longing for independence. As India gained independence, poets like A.K. Ramanujan and Nissim Ezekiel began to interrogate the complexities of postcolonial identity, exploring themes of alienation, cultural hybridity, and the tension between tradition and modernity. This study highlights how these poets navigate their identities within a global framework, blending indigenous and Western influences.